A Proposed Method for Thermal Specific Bioimaging and Therapy Technique for Diagnosis and Treatment of Malignant Tumors by Using Magnetic Nanoparticles. (20th May 2008) - Gescheit, Iddo M.; Ben-David, Moshe; Gannot, Israel
Abstract : The objective of this research program is to develop a novel, noninvasive, low-cost infrared (8–12 μ m spectral range) imaging technique that would improve upon current methods using nanostructured core/shell magnetic/noble metal-based imaging and therapies. The biocompatible magnetic nanoparticles are able to produce heat under AC magnetic field. This thermal radiation propagates along the tissue by thermal conduction reaching the medium's (tissue's) surface. The surface temperature distribution is acquired by a thermal camera and can be analyzed to retrieve and reconstruct nanoparticles' temperature and location within the tissue. The technique may function as a diagnostic tool thanks to the ability of specific bioconjugation of these nanoparticles to tumor's outer surface markers. Hence, by applying a magnetic field, we could cause a selective elevation of temperature of the targeted nanoparticles up to5 ∘ C, which detects the tumor. Furthermore, elevating the temperature over65 ∘ C and up to100 ∘ C stimulates a thermo ablating interaction which causes a localized irreversible damage to the cancerous site with no harm to the surrounding tissue. While functioning as a diagnostic tool, this procedure may serve as a targeted therapeutic tool under thermal feedback control as well.